If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 + -8x + -7 = -27 Reorder the terms: 5 + -7 + 3x + -8x = -27 Combine like terms: 5 + -7 = -2 -2 + 3x + -8x = -27 Combine like terms: 3x + -8x = -5x -2 + -5x = -27 Solving -2 + -5x = -27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -5x = -27 + 2 Combine like terms: -2 + 2 = 0 0 + -5x = -27 + 2 -5x = -27 + 2 Combine like terms: -27 + 2 = -25 -5x = -25 Divide each side by '-5'. x = 5 Simplifying x = 5
| 2-5(3+5r)=-113 | | ((7t^2)+8)/t | | -3+2x+10+x=7 | | 7y-20y-31=14y+8 | | 8(-2n+8)=160 | | 3x^2+5x+5=0 | | 3x+7.35=14.26 | | 6+2(-3)=-3+5+-3 | | 2g+a/x=4w | | 6(4x-9)-4=6(x-4)+56 | | 9x-3+4x-4=-59 | | k/14=0 | | x+6=8+7x | | 3u^2-12u+13=0 | | 0.5x+8/7x=x+36 | | 12x-1+1+2x=14 | | 3x-15+5x+59=180 | | -15=-3x+6 | | -2x+5(8x-6)=9-x | | -12=8+(f/2) | | 24x+4+2=3(10x-1) | | 2/3p+1/2=p-3 | | 6(x+3)-(4x-4)= | | (x+9)(x-3)=(x+1) | | 8(-8+5b)+6=222 | | 5+5p=-30 | | 5n-(9-5n)=9 | | 2(x+3)=8(x-1) | | 21q+73=62q-51+8q | | B=(d/1-r) | | 8n+21n=-3 | | (25/8)(24/5) |